The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/2014gl062792
|View full text |Cite
|
Sign up to set email alerts
|

Shallow crustal permeability enhancement in central Japan due to the 2011 Tohoku earthquake

Abstract: Pore pressure decreased at the Kamioka mine in central Japan after the Tohoku earthquake (M9.0) on 11 March 2011, which can be attributed to a permeability increase. We focus on the Earth's tidal response before and after the earthquake to evaluate rock permeability change through hydraulic diffusivity change. If we assume a constant elastic modulus, hydraulic diffusivity is found to increase from 3.3 to 6.7 m 2 /s after the Tohoku earthquake. We also analyzed data before and after the 2007 Noto Hanto (M6.9) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…However, the Hsieh model does not apply when the phase shift between the water level and the tidal strain is positive (a positive phase shift indicates that the water level response precedes the tidal strain [ Roeloffs , ]). Roeloffs [] proposed that a positive phase shift results from the diffusion of pore pressure to the water table (the aquifer is not well confined); the degree of confinement controls the frequency response of the pore pressure to tidal loading [ Kinoshita et al ., ]. In addition, the relationship between phase shift and hydraulic diffusivity can be written as [ Doan et al ., ] (see more details in Text S2 in the supporting information): p(),zω=italicBKuε()1eprefix−()1+iztrue/2Dtrue/ω where p ( z , ω ) is the pore‐pressure fluctuation at depth z ; B is Skempton's coefficient; K u is the bulk modulus of the saturated rock under undrained conditions; ɛ is the change in the volumetric strain; D is hydraulic diffusivity; and ω is the frequency of fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Hsieh model does not apply when the phase shift between the water level and the tidal strain is positive (a positive phase shift indicates that the water level response precedes the tidal strain [ Roeloffs , ]). Roeloffs [] proposed that a positive phase shift results from the diffusion of pore pressure to the water table (the aquifer is not well confined); the degree of confinement controls the frequency response of the pore pressure to tidal loading [ Kinoshita et al ., ]. In addition, the relationship between phase shift and hydraulic diffusivity can be written as [ Doan et al ., ] (see more details in Text S2 in the supporting information): p(),zω=italicBKuε()1eprefix−()1+iztrue/2Dtrue/ω where p ( z , ω ) is the pore‐pressure fluctuation at depth z ; B is Skempton's coefficient; K u is the bulk modulus of the saturated rock under undrained conditions; ɛ is the change in the volumetric strain; D is hydraulic diffusivity; and ω is the frequency of fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…The available data (Liao et al, 2011;Lai et al, 2014;Gong, 2009;Tang et al, 2013) show no relationship between the phase shift change and the length of the screened section. Previous field studies show that the time required for permeability recovery observed in the field usually ranges from weeks to years (Davis et al, 2001;Kinoshita et al, 2015;Manga et al, 2012;Manga and Rowland, 2009;Shi et al, 2013c;Xue et al, 2013), but in some cases perhaps as short as minutes (Geballe et al, 2011). Laboratory experiments, in contrast, document that permeability recovery can finish in tens of minutes (Candela et al, 2014(Candela et al, , 2015Elkhoury et al, 2011) but with a sensitivity to flow rate (Candela et al, 2015).…”
Section: Mechanism Of Dynamic Strain Induced Permeability Changesmentioning
confidence: 99%
“…We could not identify a cause for the slight increase in permeability after 2003. Xue et al (2013) reported that permeability in the Wenchuan earthquake fault zone in China was enhanced by the occurrence of remote earthquakes, and Kinoshita et al (2015) suggested that the 2011 Tohoku earthquake caused enhanced permeability in a mine in central Japan. In the Nojima fault, there is no convincing evidence that the permeability enhancement was due to notable earthquakes.…”
Section: Discussionmentioning
confidence: 99%